A study on integral transforms of the generalized Lommel-Wright function - Khan, Mohammad Saeed; Haq, Sirazul; Khan, Moharram Ali; Fabiano, Nicola (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/purpose: The aim of this article is to establish integral transforms of the generalized Lommel-Wright function. Methods: These transforms are expressed in terms of the Wright Hypegeometric function. Results: Integrals involving the trigonometric, generalized Bessel function and the Struve functions are obtained. Conclusions: Various interesting transforms as the consequence of this method are obtained.